2001
DOI: 10.1046/j.1365-2850.2001.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and job satisfaction in mental health nursing: focused interventions through evidence‐based assessment

Abstract: In the UK, over 20 contemporaneous reports have shown that between one-quarter and one-half of National Health Service (NHS) staff report significant personal distress (Weinberg & Creed 2000). There exists a substantial body of evidence to suggest that high levels of stress are endemic throughout the NHS (Anderson et al. 1996), and that many of these stressors may be unique to health care (Payne & Firth-Cozens 1987, Calboun & Calboun 1993). Historically, responsibility for stress management has often been plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
14

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 36 publications
2
55
0
14
Order By: Relevance
“…This somewhat exhaustive list can be particularly relevant to nursing (Arnold et al, 1998;Cotrell, 2001). In a study already discussed by Charnley (1999) relating to occupational stress in the newly qualified nurse, the author asserts that low levels of confidence in clinical skills contribute to stress in the newly registered nurse and revealed four main contributory factors.…”
Section: Sources Of Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…This somewhat exhaustive list can be particularly relevant to nursing (Arnold et al, 1998;Cotrell, 2001). In a study already discussed by Charnley (1999) relating to occupational stress in the newly qualified nurse, the author asserts that low levels of confidence in clinical skills contribute to stress in the newly registered nurse and revealed four main contributory factors.…”
Section: Sources Of Stressmentioning
confidence: 99%
“…While workload can be attributed as a stressor in all professions (Arnold et al, 1998) it has particular relevance to nursing (Arnold et al, 1998;Cotrell, 2001;Nolan and Ryan, 2008). Both groups identified excessive workload as a major source of stress in the clinical environment.…”
Section: Excessive Workloadmentioning
confidence: 99%
“…The poor psychological health and the high levels of sickness absence within the healthcare professions are likely to lead to a poorer quality of patient care [3]. Borrill et al (1996) surveyed over 11000 NHS staff and found more than 28% of the nurses suffered at least minor mental health problems [14]. Wall et al, (1997) found that 27% of the health care staff suffered serious psychological disturbances as compared to 18% of the general working population [12].…”
Section: Others Sectionmentioning
confidence: 99%
“…Nurse's environmentcare [11], Stress is acknowledged to be one of the main causes of absence from work [12]. Anxiety, frustration, anger and feelings of inadequacy, helplessness or powerlessness are emotions often associated with stress [13].…”
Section: Introductionmentioning
confidence: 99%